(untitled) (Malaysian Journal of Learning and Instruction, 2017)
Purpose – This paper presents the results of a study that sought to determine teacher conceptions of classroom management and control. The study explored classroom management knowledge of participants, and how the knowledge was gained. It also investigated the extent to which participants held various conceptions, including rule-based, dominance and nurturance conceptions, about how teachers established and maintained classroom control. Methodology – A mixed method involving a rating scale for the quantitative component, and response to open-ended interview questions for the qualitative component were used. The responses from the subjects were recorded, and notes were also taken. The data were first transcribed and double-checked for grammatical errors. The methods used to identify emerging common themes across respondents were the constant comparison and analytic induction methods. Findings – The major finding of the study was that rule-based conceptions were predominant. In their responses to open-ended questions, virtually all teachers mentioned rule-based conceptions, especially the consistent setting and monitoring of rules as being important to the teacher’s ability. The alternative conceptions of dominance and nurturance were expressed by a few of the teachers. Even teachers who showed agreement with either the dominance or nurturance conceptions showed strong support for rule-based conceptions Significance – The significance of this study to classroom practice is that knowing how to manage the classroom is one of the most important traits of quality instruction. Therefore it is important that teachers – both new and veteran –find the best way to manage their classroom in order to create a serene atmosphere for quality learning to take place.